2013
DOI: 10.1371/journal.pone.0082652
|View full text |Cite
|
Sign up to set email alerts
|

RNA Silencing Is Resistant to Low-Temperature in Grapevine

Abstract: RNA silencing is a natural defence mechanism against viruses in plants, and transgenes expressing viral RNA-derived sequences were previously shown to confer silencing-based enhanced resistance against the cognate virus in several species. However, RNA silencing was shown to dysfunction at low temperatures in several species, questioning the relevance of this strategy in perennial plants such as grapevines, which are often exposed to low temperatures during the winter season. Here, we show that inverted-repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(55 reference statements)
2
13
0
Order By: Relevance
“…Furthermore, while CHH methylation varied with temperature at both DCL3- and CMT2-dependent DMRs ( Figure 5 ), DCL3-dependent DMRs were much more strongly associated with previously identified temperature DMRs (4703 out of 10,138 DCL3-dependent DMRs, or 46%, overlapped temperature-sensitive DMRs, whereas the corresponding numbers for CMT2-dependent DMRs were 2299 out of 33,422, or 7%; Fisher's exact p-value < 2.2e-16), suggesting that much of the temperature variation in CHH methylation is due to components of the RdDM pathway. This result is consistent with previous findings showing that RNA silencing is less active at lower temperatures ( Romon et al, 2013 ).
10.7554/eLife.05255.010 Figure 5.
…”
Section: Mainsupporting
confidence: 94%
“…Furthermore, while CHH methylation varied with temperature at both DCL3- and CMT2-dependent DMRs ( Figure 5 ), DCL3-dependent DMRs were much more strongly associated with previously identified temperature DMRs (4703 out of 10,138 DCL3-dependent DMRs, or 46%, overlapped temperature-sensitive DMRs, whereas the corresponding numbers for CMT2-dependent DMRs were 2299 out of 33,422, or 7%; Fisher's exact p-value < 2.2e-16), suggesting that much of the temperature variation in CHH methylation is due to components of the RdDM pathway. This result is consistent with previous findings showing that RNA silencing is less active at lower temperatures ( Romon et al, 2013 ).
10.7554/eLife.05255.010 Figure 5.
…”
Section: Mainsupporting
confidence: 94%
“…Recently, Romon et al . () observed that the RNA silencing machinery of grapevine is resistant to low temperatures, contrary to that of herbaceous species such as N. benthamiana or A. thaliana . The RNAi strategy is therefore relevant for conferring virus resistance in this perennial crop which is often subjected to low temperatures.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 97%
“…As shown by transient expression in N. benthamiana, amiRNA constructs based on grapevine miRNA precursors can also efficiently target grapevine viral sequences (Roumi et al, 2012). Recently, Romon et al (2013) observed that the RNA silencing machinery of grapevine is resistant to low temperatures, contrary to that of herbaceous species such as N. benthamiana or A. thaliana.…”
Section: A First Step Towards Crop Improvementmentioning
confidence: 99%
“…4), still following the same research action method. The biologists, who studied vine health in laboratories (Romon et al 2013), started addressing the issue in a more holistic way. In collaboration with the group, the project deals with the vineyards in their environment.…”
Section: The Argonaut and The Tetrahedron Put To The Test With New Qumentioning
confidence: 99%